World Bank Research Digest, Vol. 2(2) - World Bank (Washington, DC, 2014)
In this issue: infrastructure and growth in developing countries; focus: finance for all? Policies and pitfalls in expanding access; exports and productivity: comparable evidence for 14 countries; local inequality and project choice; what matters to African firms? Work-related migration and poverty reduction; and economic effects during outbreaks of infectious disease.